When we are worried, what are we thinking? Anxiety, lack of control, and conspiracy beliefs amidst the COVID‐19 pandemic - Šrol, Jakub; Ballová Mikušková, Eva; Čavojová, Vladimíra (Applied cognitive psychology, 2021)
Societal crises and stressful events are associated with an upsurge of conspiracy beliefs that may help people to tackle feelings of lack of control. In our study (N = 783), we examined whether people with higher feelings of anxiety and lack of control early in the COVID‐19 pandemic endorse more conspiracy theories. Our results show that a higher perception of risk of COVID‐19 and lower trust in institutions' response to the pandemic were related to feelings of anxiety and lack of control. Feeling the lack of control, but not anxiety, independently predicted COVID‐19 conspiracy theory endorsement. Importantly, COVID‐19 conspiracy beliefs were strongly correlated with generic conspiracy and pseudoscientific beliefs, which were likewise associated with the feeling of lack of control and lower trust in institutions. The results highlight that considering people's emotional responses to the COVID‐19 pandemic is crucial for our understanding of the spread of conspiracy and pseudoscientific beliefs.